Evaluating the Performance of HEC-RAS in Simulating Strongly Nonlinear and Dispersive Wave Propagation - Rahmanto, Fiqih; Wicaksono, Albert (Fakultas Teknik Universitas Tanjungpura, 2025)
Understanding wave propagation, particularly in shallow water where nonlinear and dispersive effects become prominent, is essential for achieving accurate hydraulic modeling. HEC-RAS is a widely utilized computational tool in engineering applications for simulating open channel flows, predominantly under the assumption of hydrostatic pressure. This study investigates the capability of HEC-RAS to simulate wave propagation under conditions characterized by strong nonlinearity and dispersion. To conduct this evaluation, three benchmark scenarios were modeled: (1) solitary wave propagation in a flat, frictionless channel, (2) interaction of a solitary wave with a submerged bar, based on experimental data, and (3) regular wave propagation. Each case was simulated using HEC-RAS and the results were compared against analytical solutions or experimental observations. The findings indicate that HEC-RAS exhibits notable limitations in accurately representing wave phenomena dominated by nonlinear and dispersive effects. These limitations are primarily attributed to the shallow water equations implemented in the model, which omit non-hydrostatic pressure components. Such components are critical for maintaining wave shape and amplitude, particularly over variable bathymetry. In conclusion, while HEC-RAS remains a robust and reliable tool for conventional flow modeling, it is not well-suited for scenarios involving strongly nonlinear and dispersive wave propagation. For such cases, alternative modeling approaches that incorporate non-hydrostatic pressure effects are recommended to ensure greater simulation accuracy.